Artifact characterization of Nitinol needles in magnetic resonance imaging-guided musculoskeletal interventions at 3.0 tesla: a phantom study - Vanessa Franziska Schmidt; Olaf Dietrich; Max Seidensticker; Moritz Wildgruber; Bernd Erber; Jens Ricke; Sophia Samira Goller (Diagnostic and Interventional Radiology, 2023)

(untitled)
PURPOSETo characterize the artifacts of an 18-gauge coaxial nickel-titanium needle using a balanced steady-state free precession sequence in magnetic resonance imaging-guided interventions at 3.0 tesla.METHODSThe influence of flip angle (FA), bandwidth, matrix, slice thickness (ST), and read-out direction on needle artifact behavior was investigated for different intervention angles (IA). Artifact diameters were rated at predefined positions. Subgroup differences were assessed using Bonferroni-corrected non-parametric tests and correlations between continuous variables were expressed using the Bravais–Pearson coefficient. Interrater reliability was quantified using intraclass correlation coefficients (ICCs), and a contrast-enhanced target lesion to non-enhanced muscle tissue contrast ratio was quantified.RESULTSThe artifact diameters decreased with an increase in FA for all IAs (P < 0.001) and with an increase in ST for IAs of 45°–90° (all P < 0.05). Tip artifacts occurred at low IAs (0°–45°) and gradually increased in size with a decrease in IA (P = 0.022). The interrater reliability was high (ICC: 0.994–0.999). The contrast-enhanced target lesion to non-enhanced muscle tissue contrast ratio presented positive correlations with increasing FAs and matrices (P < 0.001; P = 0.003) and a negative correlation with increasing STs (P = 0.007).CONCLUSIONTo minimize needle artifacts, it is recommended to use FAs of 40°–60°, a ST of >7 mm, and, if possible, an IA of 45°–60°. The visibility of the target lesion and the needle’s artifact behavior must be weighed up against each other when choosing the ST, while higher FAs (40°–60°) and matrices (224 × 224/256 × 256) are associated with low artifacts and sufficient lesion visibility.